A 35-Year-Old Male with Virocid-Chemical Disinfectant Poisoning - Khanum, Easnem; Islam, Ashraful; Akter, Rahima; Mondol, Kanti; Hoque, Md Rezaul (Journal of Enam Medical College, 2019)
Virocid is a highly concentrated potent broad-spectrum disinfectant which is used in different sectors such as animal husbandry (poultry, pigs, cattle), agriculture, food processing, hospitals, horticulture, animal transport, feed storage, fish farming, personal hygiene etc. Here we report a case of a 35-year-old male poultry owner who attempted suicide following ingestion of about 10 mL of virocid (chemical disinfectant) and presented with severe burning sensation from throat to the epigastric region, abdominal pain, generalized muscle weakness, several episodes of vomiting and respiratory distress. The patient was treated conservatively along with mechanical ventilator support. After improving condition on 3rd day ventilator support was withdrawn and patient was shifted to step-down ICU. On 4th day the patient was transferred to general ward after consulting with psychiatrist and was discharged on the next day with an advice to follow-up every seven days interval. Two weeks later he was found quite normal. J Enam Med Col 2019; 9(3): 193-196